How Adolescents, Mothers, and Fathers Qualitatively Describe Their Experiences of Co-Occurrent Problems: Intimate Partner Violence, Mental Health, and Substance Use - Lessard, Geneviève (Journal of interpersonal violence, 2021)
This qualitative study examines the perceptions of mothers, fathers, and adolescents on the relations they see between intimate partner violence, mental health and substances use parental problems that co-occur in their family, and the mothers’ and fathers’ associated parenting challenges. The sample was composed of 43 people (15 mothers, 16 fathers, and 12 adolescents) who were directly affected by the co-occurrence of intimate partner violence and mental health or substances use parental problems. The participants were recruited with the collaboration of public and community organizations in the Province of Québec (Canada). The data were collected through semi-structured interviews and combined with a table detailing the specific problems identified by the participants. A thematic content analysis method was employed to do the coding, and a summary of the results was returned to some participants who agreed to collaborate with the validation of the results. The analysis revealed numerous and diverse relations between the interviewees’ co-occurring problems, but two principal patterns emerged. The first one was chiefly observed in the comments made by mothers and adolescents who saw the co-occurring problems as being the consequence of the intimate partner violence on the mother. The second pattern was largely observed in the fathers’ comments, who explained that the substance use problems came before the intimate partner violence and acted as an aggravating factor. The co-occurrence of intimate partner violence with other parental problems strongly affected the mothers’ and fathers’ parenting, making it more difficult to meet the children’s needs. Considering the complexity and diversity of the experiences and needs of the mothers, fathers, and children in co-occurring situations, future studies should evaluate the services provided to these families and the coordination between the different concerned organizations.